Inside Back Cover: Ruthenium Complex "Light Switches" that are Selective for Different G‐Quadruplex Structures (Chem. Eur. J. 2/2016). Issue 2 (18th December 2015) - Wachter, Erin; Moyá, Diego; Parkin, Sean; Glazer, Edith C.
Abstract : Two distinct "light switch" molecules are turned on in the presence of different G‐quadruplex DNA structures. When irradiated with visible light, the photochemical "light switch" undergoes selective ligand loss when bound to mixed‐hybrid G‐quadruplex DNA, followed by DNA metalation. The photophysical "light switch" brightly emits when bound to parallel G‐quadruplex DNA. More information can be found in the Full Paper by E. C. Glazer et al. onpage 550 ff.